2002
DOI: 10.1103/physrevlett.88.047201
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Splitting and Charge Carrier Spin Polarization in EuO

Abstract: High quality thin films of the ferromagnetic semiconductor EuO have been prepared and were studied using a new form of spin-resolved spectroscopy. We observed large changes in the electronic structure across the Curie and metal-insulator transition temperature. We found that these are caused by the exchange splitting of the conduction band in the ferromagnetic state, which is as large as 0.6 eV. We also present strong evidence that the bottom of the conduction band consists mainly of majority spins. This impli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
181
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(202 citation statements)
references
References 22 publications
21
181
0
Order By: Relevance
“…Among these, EuO presents the largest conduction-band exchange splitting, ∼0.54 eV, below the material's Curie temperature of 69 K. [14][15][16] In EuO, the divalent Eu ions possess a large local moment originating from the half-filled 4f band (μ Eu = 7μ B ). An energy gap of 1.0 eV separates the half-filled majority Eu-4f band from the Eu-5d conduction band.…”
Section: T (E) ∝ Exp[−2κ( E)t] With κ( E) = √mentioning
confidence: 99%
“…Among these, EuO presents the largest conduction-band exchange splitting, ∼0.54 eV, below the material's Curie temperature of 69 K. [14][15][16] In EuO, the divalent Eu ions possess a large local moment originating from the half-filled 4f band (μ Eu = 7μ B ). An energy gap of 1.0 eV separates the half-filled majority Eu-4f band from the Eu-5d conduction band.…”
Section: T (E) ∝ Exp[−2κ( E)t] With κ( E) = √mentioning
confidence: 99%
“…9 Recent studies of spin-resolved x-ray absorption spectroscopy have shown a spin-split conduction band of about 0.6 eV in its ferromagnetic state, creating a nearly 100% spin polarized electrons close to the conduction band edge. 10 Although the stoichiometric EuO has a Curie temperature (Tc) of 69 K, Tc can be enhanced significantly by pressure, [11][12][13] interfacial strain 14 or electron doping via rare-earth atoms [15][16][17][18][19][20][21][22][23][24] or oxygen vacancies. 15,16,[23][24][25] The integrations of EuO with Si, 18,[23][24][25][26][27] GaAs, 28 and GaN 18 have been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A particularly attractive candidate ferromagnetic semiconductor is europium oxide (EuO), which is known to possess nearly spin-polarized bands. 85,86 EuO becomes ferromagnetic below 70K under ambient pressure and the Curie temperature is known to increase with pressure reaching 200K under 1.5 × 10 5 atmospheres. 87 Since its integration with with Si and GaN, 86 EuO has garnered much attention for its potential use in spintronic applications.…”
Section: Topological Superconductivity and Majorana Fermionsmentioning
confidence: 99%